2013
DOI: 10.1590/s1519-69842013000300011
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection by anurofauna community at rocky seashore in coastal Atlantic Forest, Southeastern Brazil

Abstract: Rocky seashores are low granitic hills distributed along the southeastern Brazilian coast with xeric-like vegetation due to the shallow soil. Knowledge on amphibian communities and their reproductive patterns is especially reduced on this kind of environment. Herein, we present a framework of two years monitoring an amphibian community at a rocky seashore environment located at the protected area of Parque Estadual da Serra da Tiririca, municipality of Niterói, state of Rio de Janeiro, Brazil. We conducted diu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In addition, another study have showed that the structure of the plants (0) influences bromeliad selection by Ololygon argyreornata (Pederassi et al, 2012). The structure of bromeliads are related to the capability to accumulate rainwater (Pontes et al, 2013). In this way, the bromeliads of the genus Aechmea seem to be the most important plants for the local frog assemblage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another study have showed that the structure of the plants (0) influences bromeliad selection by Ololygon argyreornata (Pederassi et al, 2012). The structure of bromeliads are related to the capability to accumulate rainwater (Pontes et al, 2013). In this way, the bromeliads of the genus Aechmea seem to be the most important plants for the local frog assemblage.…”
Section: Discussionmentioning
confidence: 99%